PENGEMBANGAN BAHAN AJAR BAHASA ARAB BERBASIS KOMUNIKATIF UNTUK MAHASISWA PROGRAM STUDI KEPERAWATAN STIKES PURNA BHAKTI HUSADA BATUSANGKAR - NURLAILA NURLAILA (Ta'dib, 2011)
The aim of this study was to produce valid, practical and effective Arabic instructional materials for students majoring in nursing department of STIKES Purna Bhakti Husada Batusangkar. This study employed research and development design, especially IDI (instructional development institute) which consisted of three phase analysis: front-end analysis, prototype and assessment. The findings of the study showed that the instructional materials were valid both in terms of content and construct, practical and effective.Kata kunci: bahan ajar, komunikatif, keperawatan, penelitian pengembangan